2007
DOI: 10.1111/j.1365-2206.2006.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Congruence and co‐operation in social workers’ assessments of children in need

Abstract: This paper examines the concepts of congruence and co‐operation in social work practice with children and families. It describes findings from the author’s own research and attempts to deconstruct the interaction of the two phenomena. Using material from other published research, the paper proposes a model and suggests methods for analysing congruence and co‐operation in the practice context. The key implication is that the depth of a social worker’s understanding of a family situation may affect his or her as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 10 publications
1
28
0
4
Order By: Relevance
“…Quand le pouvoir décisionnel n'est pas partagé et reste l'apanage des éducateurs (power over), cela produit de la part des familles une réponse de l'ordre de la lutte ou du faire-semblant, faisant ainsi obstacle à l'obtention de résultats et de changements. Au contraire, quand la relation se manifeste grâce au partage du pouvoir décisionnel (power with), on observe alors des comportements de « co-opération », ce qui permet d'atteindre plus facilement les objectifs de l'intervention (Platt, 2007).…”
Section: Construire Une Relation De Confiance Avec Les Parentsunclassified
See 1 more Smart Citation
“…Quand le pouvoir décisionnel n'est pas partagé et reste l'apanage des éducateurs (power over), cela produit de la part des familles une réponse de l'ordre de la lutte ou du faire-semblant, faisant ainsi obstacle à l'obtention de résultats et de changements. Au contraire, quand la relation se manifeste grâce au partage du pouvoir décisionnel (power with), on observe alors des comportements de « co-opération », ce qui permet d'atteindre plus facilement les objectifs de l'intervention (Platt, 2007).…”
Section: Construire Une Relation De Confiance Avec Les Parentsunclassified
“…D'autre part, différents auteurs soulignent que les parents et les enfants désirent être écoutés et pris en considération par rapport à leurs propres situations où ils sont capables de fournir des aperçus importants sur leurs propres besoins et sur les changements désirés (Fernandez, 2009;Walsh, 1998). C'est à l'éducateur de trouver les stratégies, les interventions permettant de raccourcir cette distance, étant donné que la compréhension des points de vue et la construction d'un récit partagé sur les difficultés de la famille peuvent réussir à impliquer le parent dans l'intervention, avec un effet positif autant pour l'intervention elle-même que pour les résultats de l'intervention (Berry, 1992;Dawson et Berry, 2002;Darlington et al, 2010;Dumbrill, 2006;Platt, 2007).…”
Section: La Participation Des Parents Dans La Définition Et La Réalisunclassified
“…Secondly, they highlighted congruent worker-client communications and relationships as a powerful intervention tool in child protection work. It is widely noted that in most instances, children are better protected when workers and parents build a collaborative relationship and work in alliance (Dumbrill and Lo, 2009;Platt, 2007;D'Cruz and Gillingham, 2014). The family informed insights are quite significant as most child protection studies have examined the case worker-client relationship from the perspective of service providers, but there are limited studies that examine the phenomena from the perspective of service users (Altman, 2008;Yatchmenoff, 2005).…”
Section: Child Protection Policies and Investigationsmentioning
confidence: 99%
“…Platt (2007) noted the case worker's congruent and cooperative relationship with the clients was the prime factor that influences the quality of child protection intervention and outcomes. Farmer and Owen (1998) (Ghaffar et al, 2012;Harris, 2012;Dale, 2004).…”
Section: Engagement With Familiesmentioning
confidence: 99%
“…Studies have shown that parents are discouraged when the complexity of their lives and the challenges that they face to their parenting are not recognised (Featherstone & Fraser, 2012;Platt, 2007). For example, Forrester and colleagues' (2012) English study, in which workers responded to case vignettes, found that the majority of workers imposed or negotiated their own agenda on parents rather than incorporating the parent's perspective.…”
Section: Factors That Impact Parent Engagementmentioning
confidence: 99%